Revocation of The Attachment III of The Presidential Regulation Number 10 of 2021 in The Perspective of Human Rights and Maqasid Al-Shari‘ah - Sanuri Sanuri (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2021)
This research is based on a decision of the President of the Republic of Indonesia, Joko Widodo, by revoking the Attachment III of the Presidential Regulation Number 10 of 2021 concerning the business sector of investment in the liquor and alcoholic drink industry. This presidential decree attracts a wide attention from all levels of Indonesian society. Most of them welcome the decision, and a few are more optimistic about the implementation of the presidential regulation because it has actually offered a clear and proportional regulation. To get a sharp analysis result, the researcher looks at this constitutional fact through the theory of human rights and maqasid al-shari’ah. Based on the research results, it is stated that the decision of the President of the Republic of Indonesia by abolishing the presidential regulation is in line with the basic values ​​and principles contained in human rights and maqasid al-shari’ah. Even so, there are some basic rights points that need serious attention from the government, particularly how to revive the people’s economy which is teetering due to the Covid-19 pandemic. At least, this is the reason for arguing for groups who are oppossing to the presidential decision.   Abstrak: Penelitian ini bertumpu pada sebuah keputusan Presiden Republik Indonesia, Joko Widodo, dengan mencabut Lampiran III Peraturan Presiden Nomor 10 Tahun 2021 tentang bidang usaha penanaman modal dan investasi industri minuman keras dan minuman beralkohol. Keputusan presiden ini cukup mengundang perhatian dari seluruh lapisan masyarakat Indonesia. Sebagian besar dari mereka menyambut gembira keputusan itu, dan sebagian kecil lebih optimis dengan pemberlakuan peraturan presiden itu karena sebenarnya telah menawarkan suatu regulasi yang jelas dan proporsional. Untuk mendapatkan hasil analisis yang tajam, peneliti melihat fakta konstitusi ini melalui teori Hak Asasi Manusia dan maqasid al-shari’ah. Berdasarkan hasil penelitian menyatakan bahwa keputusan yang diambil Presiden Republik Indonesia dengan menghapus peraturan presiden itu sejalan dengan nilai-nilai dan prinsip-prinsip dasar yang tertuang dalam hak asasi manusia dan maqasid al-shari’ah. Meskipun demikian, ada beberapa poin hak-hak dasar yang perlu mendapatkan perhatian serius dari pemerintah terutama bagaimana membangkitkan perekonomian rakyat yang tertatih-tatih akibat pandemic Covid-19. Setidaknya, inilah yang menjadi alasan mendasar kelompok yang berseberangan dengan keputusan presiden tersebut.